Tính \(L=\lim\sqrt{n}\left(\sqrt{n+1}-\sqrt{n}\right)\).
\(0\) | |
\(\dfrac{1}{2}\) | |
\(\dfrac{1}{3}\) | |
\(\dfrac{1}{4}\) |
Chọn phương án B.
Dùng máy tính cầm tay:
Chọn phương án B.
\(\begin{aligned}
L&=\lim\sqrt{n}\left(\sqrt{n+1}-\sqrt{n}\right)\\
&=\lim\sqrt{n}\dfrac{\left(\sqrt{n+1}-\sqrt{n}\right)\left(\sqrt{n+1}+\sqrt{n}\right)}{\sqrt{n+1}+\sqrt{n}}\\
&=\lim\sqrt{n}\dfrac{\left(n+1\right)-n}{\sqrt{n\left(1+\dfrac{1}{n}\right)}+\sqrt{n}}\\
&=\lim\dfrac{1}{\sqrt{1+\dfrac{1}{n}}+1}\\
&=\dfrac{1}{\sqrt{1+0}+1}=\dfrac{1}{2}.
\end{aligned}\)